Relating pore size variation of poly (ɛ‐caprolactone) scaffolds to molecular weight of porogen and evaluation of scaffold properties after degradation. Issue 4 (21st October 2013) - Columbus, Soumya; Krishnan, Lissy K.; Kalliyana Krishnan, V.
Abstract The major challenge in designing a scaffold for fabricating tissue engineered blood vessels is optimization of its microstructure for supporting uniform cellular in‐growth with good mechanical integrity and degradation kinetics suitable for long‐term implantation. In this study, we have investigated the feasibility of varying the pore size of poly(ɛ‐caprolactone) (PCL) scaffold by altering the molecular weight of porogen and studied the effect of degradation on morphological characteristics and mechanical properties of scaffolds by correlating to the extent of degradation. Scaffolds with two different pore sizes were prepared by solvent casting and particulate leaching where poly(ethylene glycol) (PEG) porogens having two molecular weights (3400 and 8000) were used and subjected to in vitro degradation in phosphate buffered saline (PBS) upto six months. Microcomputed tomography studies of scaffolds revealed narrower pore size distribution when PEG‐3400 was used as porogen and had 78% pores in the 12–24 µ range, whereas incorporation of PEG‐8000 resulted in broader distribution with only 65% pores in the same range. Degradation resulted in scaffolds with narrower pore size distribution to have better retention of morphological and mechanical characteristics compared to scaffolds with broader distribution. Gravimetric and molecular weight studies also showed that scaffold degradation in both cases was only in initial stages after 6 months and PCL scaffolds had potential to be recommended for vascular tissue engineering applications. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 789–796, 2014.